2004
DOI: 10.1038/oby.2004.169
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the Benefits of Weight Loss Programs: An Application of the Discrete Choice Experiment

Abstract: ROUX, LARISSA, CHRISTINA UBACH, CAM DONALDSON, AND MANDY RYAN. Valuing the benefits of weight loss programs: an application of the discrete choice experiment. Obes Res. 2004;12:1342-1351. Objective: Obesity is a leading health threat. Determination of optimal therapies for long-term weight loss remains a challenge. Evidence suggests that successful weight loss depends on the compliance of weight loss program participants with their weight loss efforts. Despite this, little is known regarding the attributes inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
0
46
1
3
Order By: Relevance
“…Studies identified and reviewed were published between 1996 and 2013, and came from Canada (n ¼ 7) [13][14][15][16][17][18][19], the United States (n ¼ 3) [20][21][22], the United Kingdom (n ¼ 3) [23][24][25], Scotland (n ¼ 3) [26][27][28], Australia (n ¼ 3) [29][30][31], Sweden (n ¼ 2) [32,33], Denmark (n ¼ 1) [34], Germany (n ¼ 1) [35], Italy (n ¼ 1) [36], and Spain (n ¼ 1) [37]. Two studies had multinational perspectives [38,39].…”
Section: Key Characteristics Of Studiesmentioning
confidence: 99%
“…Studies identified and reviewed were published between 1996 and 2013, and came from Canada (n ¼ 7) [13][14][15][16][17][18][19], the United States (n ¼ 3) [20][21][22], the United Kingdom (n ¼ 3) [23][24][25], Scotland (n ¼ 3) [26][27][28], Australia (n ¼ 3) [29][30][31], Sweden (n ¼ 2) [32,33], Denmark (n ¼ 1) [34], Germany (n ¼ 1) [35], Italy (n ¼ 1) [36], and Spain (n ¼ 1) [37]. Two studies had multinational perspectives [38,39].…”
Section: Key Characteristics Of Studiesmentioning
confidence: 99%
“…attitude, occupation), which are also referred to as non-health (or process) outcomes, were not considered. Previous research examining preferences towards such outcomes suggests that these are also important to participants of HP interventions [40][41][42]. Fourth, we did not address relative importance of the identified non-health outcomes compared to each other and to health outcomes captured by EQ5D-based QALYs (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous preference studies have been applied to service provision, therapy characteristics and adherence. For example, various studies on asthma, immunizations, insulin therapy, multiple myeloma, HIV, attention deficit hyperactivity disorder (ADHD) and the healthcare utilization of breast screening have used choice experiments [4,5,[7][8][9][10][11][12]. Recent studies also have used choice-experiment weighting factors for health-state utilities [13,14].…”
Section: Introductionmentioning
confidence: 99%